Analisis Pengelolaan Dana Desa Dalam Meningkatkan Perekonomian Masyarakat - Asbanu, Yohanis; Susanti; Pardamean Daulay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to analyze the management of Village Funds in improving the community's economy in South Amanuban District, South Central Timor Regency, East Nusa Tenggara. The research method uses a descriptive qualitative approach with data collection through interviews, observations, and document studies. The results of the study indicate that the management of Village Funds has been implemented in accordance with regulations, such as Permendagri No. 20 of 2018 and PMK No. 145 of 2023, but there are still obstacles in human resource capacity, transparency, and community participation. Village Fund allocations are used for infrastructure development, community empowerment, and Village-Owned Enterprises (BUMDES), but their utilization is not optimal due to budget and planning limitations. Community participation in monitoring and evaluation is still low, while village financial governance faces challenges in accountability and reporting. The research findings also reveal irregularities in the use of Village Funds, such as inappropriate development locations and abuse of authority by village officials. The conclusion of the study emphasizes the importance of increasing the capacity of village officials, transparency in management, and strengthening community participation to maximize the impact of Village Funds on local economic growth. Policy recommendations include village financial management training, stricter oversight, and a community-based approach to achieving sustainable development. Keywords: Community Economy, Village Financial Management, Village Funds, Village Governanc.